2011
DOI: 10.5194/bgd-8-10247-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Denitrification and inference of nitrogen sources in the karstic Floridan Aquifer

Abstract: Aquifer denitrification is among the most poorly constrained fluxes in global and regional nitrogen budgets. The few direct measurements of denitrification in groundwaters provide limited information about its spatial and temporal variability, particularly at the scale of whole aquifers. Uncertainty in estimates of denitrification may also lead to underestimates of its effect on isotopic signatures of inorganic N, and thereby confound the inference of N source from these data. In this study, our objective… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 70 publications
8
34
3
Order By: Relevance
“…For example, Burns et al [2009] observed linear seasonal patterns of 18 O-NO 3 À : 15 N-NO 3 À but suggested that mixing of two or more distinct sources may have caused to these patterns. In combination with other tracers, Osaka et al [2010] found little evidence of denitrification in soil-waters, whereas they showed evidence of denitrification in the shallow groundwater in their catchment, similar to other shallow groundwater studies [Bottcher et al, 1990;Heffernan et al, 2012;McMahon and Bohlke, 2006;Mengis et al, 1999].…”
Section: Progressive Denitrificationsupporting
confidence: 83%
“…For example, Burns et al [2009] observed linear seasonal patterns of 18 O-NO 3 À : 15 N-NO 3 À but suggested that mixing of two or more distinct sources may have caused to these patterns. In combination with other tracers, Osaka et al [2010] found little evidence of denitrification in soil-waters, whereas they showed evidence of denitrification in the shallow groundwater in their catchment, similar to other shallow groundwater studies [Bottcher et al, 1990;Heffernan et al, 2012;McMahon and Bohlke, 2006;Mengis et al, 1999].…”
Section: Progressive Denitrificationsupporting
confidence: 83%
“…The quick flow contribution increases at the incidence of hydrologic activity and contributes relatively diluted NO 3 − to the spring flux signal. The long residence time of water in phreatic pores could lead to net denitrification (Heffernan et al, ) as pathway results indicate that high NO 3 − concentrations from percolating epikarst water are decreased prior to export by the phreatic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…First, assimilation causes significantly less isotopic fractionation than denitrification [Karsh et al, 2014], which would presumably become even weaker under field conditions due to cellular regulation [Kritee et al, 2012] and the simultaneous occurrence of ''reverse'' fractionation from the ongoing mineralization of this organic material [M€ obius, 2013]. Second, if the NO 2 3 pool was primarily controlled by algae and macrophytes, the strong seasonal differences in aquatic plant growth (Environment Canterbury, unpublished data, 2012) would be reflected in its isotopic composition [Heffernan et al, 2012]. However, in the current study, precipitation was a stronger driver of NO 2 3 isotopic composition than season or temperature.…”
Section: Nitrate Sinksmentioning
confidence: 99%